2013
DOI: 10.1002/jmri.24456
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enrichment of spinal cord MR imaging using a ratio of T1‐weighted and T2‐weighted signals

Abstract: The T1w/T2w ratio images demonstrated increased image contrast compared with T1w and T2w images alone and, reduced inter-individual signal intensity differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Dividing the T1w signal intensity by the T2w signal intensity further increases the contrast of the myelin content and reduces the signal receiver-coil bias (Glasser and Van Essen 2011). As a result, the T1w/T2w ratio image successfully reveals signal intensity changes with age in both the brain and spinal cord (Grydeland et al 2013;Teraguchi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dividing the T1w signal intensity by the T2w signal intensity further increases the contrast of the myelin content and reduces the signal receiver-coil bias (Glasser and Van Essen 2011). As a result, the T1w/T2w ratio image successfully reveals signal intensity changes with age in both the brain and spinal cord (Grydeland et al 2013;Teraguchi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We applied this method to spinal cord MRI, and reported that the contrast between GM and WM increased up to twofold, and an age‐related signal intensity change (probably due to myelin reduction with age) could be detected (Teraguchi et al. ). Furthermore, (Grydeland et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pros ( Nakamura et al, 2022 ) and cons ( Mühlau, 2022 ) of construing this measure as an indicator of myelin content have been debated. To the authors’ knowledge, those measures have only been tested once in the SC of a single younger pwMS with a relatively short disease duration, compared to a range of control values, showing qualitative difference in lesioned tissue, but not in normal-appearing GM ( Teraguchi et al, 2014 ).…”
Section: Avenues For Future Researchmentioning
confidence: 99%
“…In parallel, there has been increasing interest in using non-invasive myelin maps, including T1w/T2w myelin maps, to make comparisons across individuals and groups, for example in healthy adults (Teraguchi et al, 2014; Shafee et al, 2015; Yang et al, 2020), over the course of development (Bozek et al, 2018; Grydeland et al, 2019; Norbom et al, 2020; Kwon et al, 2020), aging (Grydeland et al, 2013; 2019; Vidal-Piñeiro et al, 2016), in brain diseases (Teraguchi et al, 2014; Granberg et al, 2017; Rowley et al 2018; Nakamura et al, 2017; Du et al, 2019; Wei et al, 2020; Qiu et al, 2021), and for exploration of other neurobiological questions (Grydeland et al, 2016; Ma and Zhang 2017; Burt et al, 2018; Fukutomi et al, 2018; Li et al, 2019; Toschi et al, 2019; Gao et al, 2020; Liu et al, 2020; Paquola et al, 2020); however, additional considerations arise when using T1w/T2w myelin maps to address such questions. For example, although in the absence of head motion there is an exact correction of the spatially varying radiofrequency (RF) receive field (B1-) effects after taking the ratio of T1w and T2w images (either from the head coil or from the body coil after vendor receive field correction), this ratio leaves in RF transmit (B1+) field effects because they differ between the T1w and T2w images (Glasser and Van Essen 2011, and as will be discussed in Section 2.1 below).…”
Section: Introductionmentioning
confidence: 99%